Integrated Transcriptome and Proteome Analyses Reveal Protein Metabolism in Lactobacillus helveticus CICC22171 - Xu, Mengfan; Hu, Shanhu; Wang, Yiwen; Wang, Tao; Dziugan, Piotr; Zhang, Bolin; Zhao, Hongfei (Frontiers in Microbiology, 2021)
Lactobacillus helveticus is a homofermentative lactic acid bacterium. It is widely used in the fabrication of Swiss cheese and other dairy products. The aim of this study was to elucidate the mechanism by which L. helveticus utilizes protein. L. helveticus CICC22171 were cultured in two different media with various nitrogen sources. The control contained 20 basic amino acids while the experimental medium contained casein. De novo transcriptome and iTRAQ proteome analyses were applied to determine how L. helveticus utilizes protein. The casein underwent extracellular hydrolysis via ATP-binding cassette (ABC) transporter upregulation and Mn2+-associated cell envelope proteinase (CEP) downregulation. Sigma factors and EF-Tu were upregulated and Mg2+ was reduced in bacteria to accommodate DNA transcription and protein translation in preparation for proteolysis. Hydrolase activity was upregulated to digest intracellular polypeptides and control endopeptidase genes. In these bacteria, casein utilization affected glycolysis, trehalose phosphotransferase system (PTS), and key factors associated with aerobic respiration and reduced glucose consumption.